Novel CRISPR-Cas9 approach to combat with COVID-19 - Jahanzaib Ali (BIOEDUSCIENCE, 2023)
Background: The recent outbreak of Corona Virus has affected people all over the world so that WHO declared it a pandemic. This pandemic has become a major problem for people, health professionals, and research institutes that how to combat SARS-CoV-2. The objective of this review article is to provide a brief study that CRISPR/Cas9 can be used to combat SARS-CoV-2. Methods: The comparison of three genome editing techniques (ZNF, TALEN, and CRISPR/Cas9) is done. The mechanism of action of CRISPR/Cas9 is discussed. Results: The studies provided in this review article suggest that it is difficult to recognize this virus as they have their own metabolic machinery and they replicate their selves in the host cell and consume host cellular products to perform their own functions. The COVID-19 proteins may contain some specific areas that are suitable targets for therapy, such as tiny inhibitor molecules for viral polymerase, or impede the attachment of viruses to the receptor sites, for example, viral coat proteins can be used for vaccination purposes. Conclusion: CRISPR-Cas9 can be used to control the SARS-CoV-2 genome from replication and spread to other parts of the body as it can edit the genome quite efficiently. This proposed model will help in targeting the SARS-CoV-2 genome more precisely in the future.